Market Study For Improving Market Stategy (Case Study: RA Planner Bookstore) (The Indonesian Journal of Business Administration, 2021)
RA Planner Bookstore is a company that introduces new nuances to the process of maintaining a daily journal, with features such as an appealing design, ease of use, and, of course, a unique design each year. In the journal/planner product, RA Planner always tries to bring innovation with a new design, new specification, or new future. This study employs both qualitative and quantitative methodologies, with the former relying on internal analysis and the latter on the distribution of questionnaires to respondents. To validate customer value mapping, quantitative methods were utilized to deliver a questionnaire to 301 respondents.This study employs both qualitative and quantitative methodologies, with the former relying on internal analysis and the latter on the distribution of questionnaires to respondents. To validate customer value mapping, quantitative methods were utilized to deliver a questionnaire to 301 respondents. Keywords: Market study, retail business, marketing strategy